2002
DOI: 10.1046/j.1523-1755.2002.00277.x
|View full text |Cite
|
Sign up to set email alerts
|

Troglitazone suppresses the secretion of type I collagen by mesangial cells in vitro

Abstract: PPAR-alpha and -gamma mRNA signaling pathways are in place and active in mesangial cells. Both agonists affect the phenotypic behavior of mesangial cells and ameliorate changes resulting from hyperglycemia. The data indicate that the correction of mesangial cell phenotype by troglitazone may influence production/deposition of a pathological fibrotic connective tissue matrix (that is, type I collagen) by these cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
35
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 47 publications
5
35
0
1
Order By: Relevance
“…Thus, the anti-inflammatory effects of rosiglitazone may contribute to the marked renal protection in the current study. Finally, PPARg is constitutively expressed in glomeruli, particularly in mesangial cells (Nicholas et al 2001), and PPARg agonists reduce mesangial cell collagen production (Routh et al 2002). Likewise, in this study, rosiglitazone reduced intraglomerular collagen IV expression and glomerular and tubulointerstitial fibrosis.…”
Section: Discussionsupporting
confidence: 68%
“…Thus, the anti-inflammatory effects of rosiglitazone may contribute to the marked renal protection in the current study. Finally, PPARg is constitutively expressed in glomeruli, particularly in mesangial cells (Nicholas et al 2001), and PPARg agonists reduce mesangial cell collagen production (Routh et al 2002). Likewise, in this study, rosiglitazone reduced intraglomerular collagen IV expression and glomerular and tubulointerstitial fibrosis.…”
Section: Discussionsupporting
confidence: 68%
“…Of the 379 genes robustly regulated by two structurally distinct PPAR␥ agonists in EWAT of db/db mice, 33 encoded for known secreted proteins. Not surprisingly, a few genes known to be regulated by PPAR␥, such as adiponectin (Combs et al, 2002), lipoprotein lipase (Auwerx et al, 1996), laminin ␤3 (Routh et al, 2002), FGF21 (Wang et al, 2008), and TNF␣ (Singh Ahuja et al, 2001) were identified. The other genes in Table 1 were not previously associated with PPAR␥ but are known to be implicated in various pathways such as inflammation, lipid metabolism, and cell growth.…”
Section: Discussionmentioning
confidence: 99%
“…1B). A subset of the 33 genes has previously been shown to be regulated at the transcript level by PPAR␥ agonists [e.g., adiponectin (Adipoq; Combs et al, 2002), FGF21 (Fgf21; Wang et al, 2008), lipoprotein lipase (Lpl; Auwerx et al, 1996), Laminin b3 (Lamb3; Routh et al, 2002), and TNF␣ (Tnf; Singh Ahuja et al, 2001)] (Table 1). Adiponectin, FGF21, and lipoprotein lipase were up-regulated by PPAR␥ agonist treatment, whereas Laminin b3 and TNF␣ were down-regulated (Table 1).…”
Section: Identification Of Genes Encoding For Secreted Proteins Regulmentioning
confidence: 99%
“…In addition to the improved metabolic control, it is possible that PPAR␥ agonists have more direct beneficial actions on the kidney because constitutively expressed PPAR␥ are found in glomeruli, particularly mesangial cells (Asano et al, 2000;Nicholas et al, 2001) and PPAR␥ agonists reduce type I collagen synthesis in cultured glomerular mesangial cells (Routh et al, 2002;Zheng et al, 2002). In addition to directly inhibiting glomerular collagen synthesis, PPAR␥ agonist may also act indirectly, via its anti-inflammatory action.…”
Section: Ppar␥ Agonists Protect the Kidney Better Than Acei 857mentioning
confidence: 99%